Comparison of The Effect of Entrepreneurial Orientation on The Performance of SMES/MSMEs in Indonesia in The Pre-Pandemic Period and Pandemic: A Meta-Analysis Approach - Akhmad Ali Rusdi; Lily Sudhartio (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: The number of research publications examining the correlation between entrepreneurial orientation and performance in Indonesia increased significantly from January 2015 to June 2023. However, the findings have been inconsistent, with entrepreneurial orientation reported to have large, medium, small, neutral, or even negative effects on the performance of SMEs/MSMEs. This variation has led to confusion regarding the actual strength of the correlation between these two variables.Purpose: This study aims to determine the actual influence of entrepreneurial orientation on the performance of SMEs/MSMEs in Indonesia under two different turbulent business environments.Method: A meta-analysis approach was employed, utilizing secondary data sourced from research articles in Indonesia indexed in the Science and Technology Index (SINTA), Copernicus, EBSCO, Google Scholar, and Scopus.Findings: During the pre-pandemic period (Industrial 4.0 boom), entrepreneurial orientation had a positive influence on the performance of SMEs/MSMEs in Indonesia, with an effect size of r=0.25–0.34r = 0.25 – 0.34 (mean r=0.30r = 0.30, p<0.001p < 0.001). In the pandemic period, the effect size was r=0.24–0.32r = 0.24 – 0.32 (mean r=0.28r = 0.28, p<0.001p < 0.001). According to Cohen’s classification, these effects are small to moderate but significant. Subgroup analysis revealed no significant difference between the two periods (p=0.71,>0.05p = 0.71, > 0.05).Conclusion: The influence of entrepreneurial orientation on SME/MSME performance remains consistent across different turbulent business environments, with a small to moderate effect.Originality/Value (State of the Art): This study demonstrates how meta-analysis can synthesize varying research findings in the field of management to provide more robust conclusions. It offers a clearer understanding of the extent to which entrepreneurial orientation impacts the performance of SMEs/MSMEs in Indonesia. Keywords: entrepreneurial orientation, business performance, variations, meta-analysis